Development of VLF/LF Bands Interferometer and Its Initial Observations. Issue 4 (20th August 2013) - Takayanagi, Yuji; Akita, Manabu; Nakamura, Yoshitaka; Yoshida, Satoru; Morimoto, Takeshi; Ushio, Tomoo; Kawasaki, Zen‐Ichiro; Yamamoto, Kenji
Summary We have been developing an EM source location system using the VLF/LF bands based on broadband digital interferometry to monitor lightning activity in a wide area. Since EM waves in VLF/LF radiated by lightning discharges propagate a long distance, the VLF/LF interferometer locates lightning discharges a few hundred kilometers away from the VLF/LF interferometer. We conducted a lightning observation campaign using a prototype of a VLF/LF band digital interferometer and VHF band digital interferometers in Darwin, Australia. The VLF/LF radiation sources were located near those of the VHF source. We succeeded in locating the VLF/LF radiation sources associated with return strokes near the ground. © 2013 Wiley Periodicals, Inc. Electr Eng Jpn, 185(4): 9–17, 2013; Published online in Wiley Online Library (wileyonlinelibrary.com). DOI 10.1002/eej.22300